Aspek Hukum Penanganan Kekerasan Berbasis Gender di Ruang Digital Studi Perbandingan antara Indonesia dan Negara-Negara di ASEAN - Yulianingsih, Sri; Putra, Rengga Kusuma; Christiana, Titi (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Gender-based violence in digital spaces has become an escalating issue globally, impacting individuals through harassment, stalking, and unauthorized sharing of private content. This study aims to examine and compare the legal frameworks of Indonesia, India, Singapore, Malaysia, and the Philippines in addressing such violence, focusing on victim protection and enforcement effectiveness. Using a qualitative descriptive approach and comparative analysis, this research reviews primary legal documents, policies, and relevant literature to identify the strengths and limitations of each country’s approach. Findings indicate that Indonesia relies on the Domestic Violence Act (UU PKDRT) and the Women and Children Protection Unit (PPA), though limited resources and a lack of specialized training for law enforcement remain challenges. India combines strict IT regulations with public digital education campaigns, effectively raising awareness but still faces social stigma in reporting. The study highlights the importance of accessible reporting mechanisms, public awareness initiatives, and cross-country collaboration within ASEAN to enhance the effectiveness of legal protections against gender-based violence in digital spaces. This research contributes by providing insights into the contextual adaptations of legal frameworks and suggests future studies to conduct fieldwork for a deeper understanding of implementation and policy adaptation.